Development and characterization of a superhydrophobic and anti-ice asphaltic nanostructured material for road pavements - Nascimento, José Heriberto Oliveira do (2012)
Pavement engineering has been one of the emerging areas in the use of nanomaterials due to the capacity that these nanostructured materials have in modifying surfaces such as asphalt materials by properties such as water and oil repellency, anti ice, among others. The accession of the ice is correlated with the physico-chemical properties of the surface of solid materials such as asphalt. This phenomenon has serious consequences and impacts, particularly in temperate countries, inter alia, with regard to road safety and the mechanical strength of the pavement. In this work, a new asphalt material with antifreeze and super hydrophobic properties was studied and developed using nanostructured materials like surface modifier agent. The surface of asphalt material was nanocoated by wet chemical process and characterized by particle size measures using a Malvern Instruments Nanosizer. The morphological and physico-chemical properties were characterized by XPS, AFM, SEM, EDS and MEVT. The characterization as its hydrophobicity were made contact angle measures using distilled water and ice was logged behavior anti test under controlled environment at a temperature of -10° c. The samples were also subjected to wear test according to EN 10974. The results demonstrated that the asphalt material presented an excellent superhydrophobic behavior, with an angle of 163º and an inhibitor of adherence of ice. After the test of wear the superhydrophobic effect was maintained. This work constitutes a significant advance in the application of antifreeze and superhydrophobic surfaces and an important development for road engineering.